2014
DOI: 10.14260/jemds/2014/3879
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Skin Tumors in a Tertiary Care Centre in Northern India

Abstract: BACKGROUND: There is limited data on the spectrum of benign and malignant neoplasms of skin and subcutis in India. AIM: This study was undertaken in a tertiary care hospital of Uttarakhand to evaluate the frequency of various neoplasms affecting skin and subcutis in biopsy specimens. MATERIAL AND METHODS: A retrospective and prospective analysis of 660 skin biopsies was undertaken. The neoplasms were categorized as per International classification of World health Organization (WHO). RESULTS: Of all the skin bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…Head and neck regions are the most common sites of cutaneous malignancies. [ 10 ] Our study population showed similar results only for SCC and BCC. Other types like melanoma, dermatofibrosarcoma, Kaposi's sarcoma, and miscellaneous tumours had lower limb as the most common site of involvement.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Head and neck regions are the most common sites of cutaneous malignancies. [ 10 ] Our study population showed similar results only for SCC and BCC. Other types like melanoma, dermatofibrosarcoma, Kaposi's sarcoma, and miscellaneous tumours had lower limb as the most common site of involvement.…”
Section: Discussionsupporting
confidence: 68%
“…This is almost similar to the results of a study by Azad et al . [ 10 ] which had 55.8 years as mean age. [ 10 ] Several studies have indicated that 70% of all skin cancers occurred in sixth, seventh, and later decades.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…where the mean age was 55.8 years. [ 11 ] There was female preponderance with a male-to-female ratio of 1:1.53. Lal et al .…”
Section: Discussionmentioning
confidence: 99%
“…Table 3 shows comparison of various characteristics between different studies. [ 10 11 13 16 17 ] Small sample size was a major limitation of this study. Immunohistochemistry (IHC) staining and dermoscopy were not performed in all cases due to lack of resources.…”
Section: Discussionmentioning
confidence: 99%